THE PROBLEMATICS OF THE MEANING OF A CHILD'S STATUS IN NATIONAL LAW: BETWEEN LEGAL CERTAINTY AND JUSTICE - Nurini Aprilianda; Syihabuddin; Guntur Aris Prabowo (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The article titled "THE PROBLEMATICS OF THE MEANING OF A CHILD'S STATUS IN NATIONAL LAW: BETWEEN LEGAL CERTAINTY AND JUSTICE" written by the Author raises the issue of analysis regarding the view of Judges who consider justice should be prioritized over legal certainty in delivering criminal verdicts, especially against Children who conflict with the law. The Author focuses on the limitations of the criminal sentence imposed on Children, then analyzes the provision against the verdict of the Penajam State Court No. 3/Pid.Sus-Child/2024/PN Pnj which exercised judicial activism by imposing a prison sentence exceeding the provisions in Law No. 11 of 2012 on the Juvenile Justice System. The result of the research conducted by the Author is that a criminal sentence of imprisonment can be imposed on the child. If threatened with a life imprisonment or death penalty provision, then the Child can only be sentenced to a maximum of ½, so the maximum imprisonment sentence allowed is 10 years. However, this is countered by the Presiding Judge of Case Number 3/Pid.Sus-Child/2024/PN Pnj by imposing a 20-year prison sentence on Child Junaedi, prioritizing justice over legal certainty.